Intraarterial therapies for primary liver cancer: state of the art. Issue 10 (October 2013) - Chapiro, Julius; Tacher, Vania; Geschwind, Jean-François
Image-guided intraarterial therapies play an important role in the treatment of patients with hepatic malignancies. These therapies provide the dual benefit of reduced systemic toxicity and effective local tumor control. As a result, procedures such as transarterial chemoembolization have been included in the official treatment guidelines for hepatocellular carcinoma (HCC) and are fully accepted for the treatment of patients with intermediate stage disease. In this review, we will describe the scientific rationale for intraarterial therapies and discuss the available clinical evidence for primary liver cancer. Finally, we will touch on the current trends consisting of combining intraarterial approaches with systemically administered targeted agents.